Biochemical Composition of Pomegranate (Punica granatum L.) as a Natural Feed Additive - Utami, Merry Muspita Dyah; Dewi, Aryanti Candra; Hertamawati, Rosa Tri; Jasmine, Dillenia; Wafia, Nala; Saputri, Jini; Septiyanto, Kornelius Hangga (International Journal of Technology, Food and Agriculture, 2025)
Antibiotics and microbial resistance are important issues in the poultry industry. The research continues to find alternative natural feed additives to replace antibiotics and have positive effects as growth promoters. This study aimed to provide the biochemical composition of pomegranate (Punica granatum) with the object of peels, seeds (including arils), and whole fruit (peels + seeds) using six replicates for each part of the pomegranate. Eighteen pomegranates were analyzed for water, carbohydrates, protein, fat, fiber, ash, polyphenols, flavonoids, tannins, and antioxidant activity. The weight of the peel compared to the total weight was significantly higher (p≤0.05) than seeds and whole fruit. The protein, fat, and fiber levels of peels were substantially lower than those of seeds and whole fruit, in contrast, the ash content and carbohydrate levels were significantly higher (p≤0.05) than other pomegranate parts. The biochemicals and bioactive compounds in the peel tend to be higher than the different parts. The levels of polyphenols, flavonoids, tannins, and antioxidant activity in the peel were significantly (p≤0.05) higher than all parts of the pomegranate, respectively 11.3 mg/g, 9.78 mg/g, 200.52 mg/g, and 39.03%. This study concludes that the peel is the best contributor as a natural feed additive.